1999
DOI: 10.1046/j.1365-2958.1999.01590.x
|View full text |Cite
|
Sign up to set email alerts
|

Secreted aspartic proteinase (Sap) activity contributes to tissue damage in a model of human oral candidosis

Abstract: Secreted aspartic proteinases (Saps) are important virulence factors during Candida albicans mucosal or disseminated infections. A differential expression of individual SAP genes has been shown previously in a model of oral candidosis based on reconstituted human epithelium (RHE), and in the oral cavity of patients. In this study, the ultrastructural localization of distinct groups of Sap isoenzymes expressed during RHE infection was shown by immunoelectron microscopy using specific polyclonal antibodies direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
221
3
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(235 citation statements)
references
References 39 publications
7
221
3
4
Order By: Relevance
“…For this study, the clinical C. albicans wild-type isolate designated SC5314 (Gillum et al, 1984), the single mutants cph1 (Lo et al, 1997) and efg1 (Stoldt et al, 1997), the double mutant cph1/efg1 (Lo et al, 1997) and an EFG1 reconstituted strain (Lo et al, 1997) were used. For the incubation of C. albicans with PMNs and for the infection of the reconstituted epithelium, inocula were prepared as reported previously (Schaller et al, 1998(Schaller et al, , 1999.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For this study, the clinical C. albicans wild-type isolate designated SC5314 (Gillum et al, 1984), the single mutants cph1 (Lo et al, 1997) and efg1 (Stoldt et al, 1997), the double mutant cph1/efg1 (Lo et al, 1997) and an EFG1 reconstituted strain (Lo et al, 1997) were used. For the incubation of C. albicans with PMNs and for the infection of the reconstituted epithelium, inocula were prepared as reported previously (Schaller et al, 1998(Schaller et al, , 1999.…”
Section: Methodsmentioning
confidence: 99%
“…The medium was changed every 24 h. Three replicate infection experiments were performed with the C. albicans wild-type SC5314, the single mutants cph1 and efg1, the double mutant cph1/efg1 and the EFG1 revertant. Epithelia were infected with 2310 6 C. albicans yeast cells of each strain in 50 ìl PBS for 12, 36, 46 and 52 h as described previously (Schaller et al, 1998(Schaller et al, , 1999. Histological lesions of the samples caused by C. albicans were investigated by light microscopy.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These secreted enzymes degrade animal tissues and facilitate fungal growth and penetration during infections. 23,25,32,33 We performed ex vivo tongue infection assays and found that the order of growth rates for the 3 cell types was opaque cells>gray cells>white cells at both 30 C (Fig. S6A) and 37 C (Fig.…”
Section: White Gray and Opaque Cells Exhibit Different Secreted Aspmentioning
confidence: 99%